Short and practical enantioselective synthesis of linezolid and eperezolid via proline-catalyzed asymmetric alpha-aminooxylation - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
An efficient enantioselective synthesis of the antibacterials, linezolid (U-100766), and eperezolid (U-100592) using D-proline-catalyzed asymmetric alpha-aminooxylation of aldehydes as the key step is described here. This is the first report on the enantioselective synthesis of linezolid and eperezolid using asymmetric catalysis. (c) 2006 Elsevier Ltd. All rights reserved.

Short enantioselective synthesis of (-)-chloramphenicol and (+)-thiamphenicol using tethered aminohydroxylation - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugarn (Tetrahedron, 2006)
An efficient enantioselective synthesis of (-)-chloramphenicol (1) and (+)-thiamphenicol (2) is described. These antibiotics have been synthesized from commercially available 4-nitrobenzaldehyde and 4-(methylthio)benzaldehyde, respectively, using tethered amino-hydroxylation and Sharpless asymmetric epoxidation as the chirality inducing steps. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: asymmetric epoxidation; Asymmetric synthesis; Kinetic resolution; Tethered aminohydroxylation

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone via Rh-catalyzed diastereoselective oxidative C-H aminations - Narina, Srinivasarao V.; Kumar, Talluri Siva; George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An efficient enantioselective synthesis of (-)-cytoxazone (1) and (+)-epi-eytoxazone (2) using proline-catalyzed asymmetric alpha-amino-oxylation of aldehydes followed by Rh-catalyzed diastereoselective oxidative C-H amination as the key steps is described. syn or anti 1,2-aminoalcohols were obtained by Rh-catalyzed intramolecular amidation of the C-H bonds of carbamates or sulfamate esters with good to excellent diastereoselectivity. (c) 2006 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (S)-timolol via kinetic resolution of terminal epoxides and dihydroxylation of allylamines - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron, 2007)
An efficient enantioselective synthesis of (S)-timolol has been described using chiral Co-salen-catalyzed kinetic resolution of less expensive (+/-)-epichlorohydrin with 3-hydroxy-4-(N-morpholino)-1,2,5-thiadiazole in good overall yield (55%) and excellent enantioselectivity (98%). Synthesis of (S)-timolol has also been achieved using hydrolytic kinetic resolution as well as asymmetric dihydroxylation routes in 90% ee and 56% ee, respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric reactions; diols; epoxides; Kinetic resolution; oxazolidinone

NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides with high diastereoselectivity: a short route to (-)-cytoxazone and droxidopa - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letter, 2007)
The NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides was achieved using lithium bromide as the bromine source under acidic conditions at rt to afford the corresponding chiral alpha-bromo-beta-hydroxy carboxamides. Excellent yields (77-90%) and diastereoselectivities (up to 10:1) along with exclusive control over regio- as well as anti-selectivity are the main features with a good scope of substrates. The method has successfully been applied in the enantioselective syntheses of two biologically important molecules, viz (-)-cytoxazone and L-threo-DOPS (droxidopa). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric bromohydroxylation; Carboxamide; cytoxazone; droxidopa; NaIO4